PENDAMPINGAN GURU MTS DALAM PENGEMBANGAN KETERAMPILAN DIGITAL MELALUI PEMBELAJARAN STEM CODING BERBASIS BLOK - Ardianto, Didit; Lathifah, Suci; Zuraiyah, Tjut Awaliyah; Putri, Annisa; Aziz, Helmi; Amalia, Najla Nurul (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
Strengthening digital skills among teachers in STEM-based learning is an urgent need in the digital age, especially in Madrasah Tsanawiyah (MTs) environments, which often lag in technology adoption. Although constructivist learning theory emphasizes the importance of integrating technology into education, the reality shows that many teachers still struggle to implement this approach effectively. Therefore, this community service program aims to empower MTs teachers through intensive training and ongoing mentoring in the use of block-based coding applications for STEM education. The program employs a social engineering approach involving needs surveys, training, implementation workshops, and performance evaluation. The results indicate significant improvements in teachers’ skills and knowledge, with 85% of teachers showing enhanced abilities in designing STEM lessons, 89% in knowledge of block-based coding applications, and 83% in skills to create projects using these applications. In conclusion, the training successfully bridges the gap between theory and practice, though challenges such as infrastructure limitations and varying levels of initial understanding remain barriers that need to be addressed through sustained support and further development.